Possible thoracic metastasis from squamous cell carcinoma of the external auditory canal: A case report - Hiroshi Takehara; Ken Kodama; Toru Momozane; Masashi Takeda; Kaichi Shigetsu; Hiroki Kishima (Clinical Case Reports)
Key Clinical Message An 80‐year‐old never‐smoking woman, who underwent radiotherapy in combination with simultaneous intra‐arterial chemotherapy for external auditory canal squamous cell carcinoma (SCC) 10 years ago, was referred to our department due to a painful huge chest wall tumor. We conducted surgical resection combined with the right upper lobe and chest wall including the 3rd to 5th ribs and affected serratus anterior muscle. Histologically, atypical keratotic cells with the same morphology as external auditory canal SCC proliferated without the figure of carcinoma in situ or squamous dysplasia of the bronchial epithelium of the lung parenchyma adjacent to the tumor. Take Home Message: If long‐term imaging follow‐up had been performed, it would have been easier to detect it early and differentiate it from metastasis or primary lung cancer.